Exploring Gender Differences in Public Speaking Anxiety - Benni Ichsanda Rahman Hz (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Comprehending the factors that lead to public speaking anxiety is crucial; this includes gender distinction. This research was aimed at examining the levels of students' English public speaking anxiety in the context of their gender differences. This study included 63 (21 males and 42 females) English Language Education Study Program students from one of the state universities in North Sumatra. To examine this phenomenon in its natural environment, a mixing technique was used. An examination of records was utilized to collect the required data. The data was then analyzed in two distinct ways: a statistical calculation was performed on the results of 17-question student questionnaires on their level of public speaking anxiety, and a constructive analysis was performed by comparing the responses of various respondents. On average, male participants in this study reported lower levels of anxiety than female ones. The difference between 50.52 and 57.14 is substantial. â€œI am anxious that I will embarrass myself in front of the audience,â€ â€œI am anxious before speaking,â€ and â€œI am worried that my audience will think I am a poor speakerâ€ are the areas where female respondents are more anxious than male. It is necessary to do more research with a bigger number and variety of respondents.